Supernumerary tooth in Maxillary Anterior Region and its complications: A case report (Journal of Orofacial Research, 2018)
Supernumerary teeth can present in various forms and in any region of the mandible or maxilla but are more common in the anterior maxilla. These teeth may remain embedded in the alveolar bone or can erupt into the oral cavity. When it remains embedded, it may cause disturbance to the developing teeth. Early detection is an important key to avoid development of complications. This report presents a case of a 12-year-old girl with an impacted supernumerary tooth in the maxillary anterior region between the roots of right central and lateral incisor resulting in the rotation of central incisor leading to unaesthetic appearance. To prevent further complication, immediate surgical removal of the supernumerary tooth was recommended.